If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + 2) + 2x = 0 Reorder the terms: 3(2 + 5x) + 2x = 0 (2 * 3 + 5x * 3) + 2x = 0 (6 + 15x) + 2x = 0 Combine like terms: 15x + 2x = 17x 6 + 17x = 0 Solving 6 + 17x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 17x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 17x = 0 + -6 17x = 0 + -6 Combine like terms: 0 + -6 = -6 17x = -6 Divide each side by '17'. x = -0.3529411765 Simplifying x = -0.3529411765
| 10x/(2x^2) | | 10x/2x^2 | | Y=4/5×-4 | | 3t+4t+7t+6=48 | | (3y+2)(7-y)=0 | | 0.16y+0.04(y+2000)=1680 | | (6+u)(2u-7)=0 | | 0.09xX=161.14 | | 3x-3x=24 | | x^2+3x^2=4x^2 | | 5/4-7/3x | | 6y+2y=7y+9 | | 3/8b=24 | | 3(x+1.83)=2x | | 0.09xX=121.10 | | -11/9x=-1/5 | | (10x-2)=55+63 | | (3x+15)=(4x-10) | | -3/10y=-6 | | 6w+5=9w+2 | | (2x+5)=33 | | 6x+5y+2x-2y= | | .16(y-6)+.02y=.08y-.7 | | 3w+4=2w+11 | | 0.6y+6.5=0.5(9+y) | | 6p=91 | | 6x+5y+2x= | | 28-2x=34 | | (6x)+(4x-3)=46 | | -4.5x+1.1=-16.9 | | 4(2x-8)-7=4(x-4)+5 | | .7x+4.2=.6x+1.4 |